Colloidal Analysis of Particles Extracted from Microalloyed Steels - Hegetschweiler, Andreas; Jochem, Aljosha Rakim; Zimmermann, Anna; Walter, Johannes; Staudt, Thorsten; Kraus, Tobias (Particle & Particle Systems Characterization, 2021)
Different colloidal particle characterization methods are examined for their suitability to determine the particle size distribution of particles extracted from steels. Microalloyed steels are dissolved to extract niobium and titanium carbonitride particles that are important for the mechanical properties of these steels. Such particles have sizes ranging from several nanometers to hundreds of nanometers depending on the precipitation stage during the thermomechanically controlled rolling process. The size distribution of the particles is analyzed by dynamic light scattering (DLS), analytical ultracentrifugation (AUC), and hollow fiber flow field-flow fractionation (HF5) and compared to data obtained for reference particles as well as data from electron microscopy, the standard sizing technique used in metallurgy today. AUC and HF5 provide high-quality size distributions, average over large particle numbers that enables statistical analysis, and yield useful insights for alloy design; however, DLS fails due to a lack of resolution. Important aspects in the conversion and comparison of size distributions obtained for broadly distributed particle systems with different measurement principles and the role of surfactants used in sample preparation are discussed.
CRIS-Team Scopus Importer:2021-06-18
Keywords: colloidal analysis; microalloyed steels; niobium carbonitrides; precipitate analysis; titanium carbonitrides